An anticancer agent - Othman, Fauziah; Rahmat, Asmah; Endrini, Susi; Jakfa, Suherman; Wan Mohamad Zain, Wan Nor I'zzah (2009)

(untitled)
The present invention relates to Cola nitida, an anticancer agent, the anticancer properties include antioxidant activities: FTC, TBA, and DPPH; antioxidant minerals: oxygen, carbon, potassium, phosphorus and magnesium; total phenolic and total flavonoid content.